Speech acts and discourse strategies in the management of disagreement in group discussion among Malaysian learners of english - Engku Safruddin, Engku Muhammad Syafiq (2022)
Having the knowledge of communicative actions and the ability to use language appropriately according to the context (pragmatic competence) is paramount in communication. It stresses how important it is for us to perform well because pragmatic skills are essential to be developed in order for us to communicate appropriately. Communicative activities such as argumentation demands us to meet the pragmatic needs required to engage in the discourse, whether in the first language (L1) or in second language (L2). This is because not everyone shares similar opinions on any topic. Thus, managing disagreement is necessary for preserving the flow of conversation by being able to voice differences effectively. The scarcity of studies on disagreement in multi-person interactions, and the lack of naturalinteraction data in studies of disagreement, have inspired this study. This study tries to explore how Malaysian ESL learners perform disagreement when speaking in English. This study is a descriptive case study. It adopts discourse analysis using pragmatics as the approach to investigate how disagreement is structured linguistically through the lens of speech acts and discourse strategies. It utilises data from eight group discussions involving 32 upper-intermediate level Malaysian ESL learners in a Malaysian higher education setting. The group discussion activity required the ESL learners to perform group discussions in a group of four persons each on a controversial topic that needed them to express their opinions. Findings indicate that the participants employed complex arrangement patterns of speech acts. These speech acts consist of multiple linguistic discourse strategies at the discourse marker level, propositional strategies, turn-taking patterns, as well as the argumentative structure of disagreement. From these patterns of speech acts and discourse strategies, this study uncovers how the participants managed their disagreement in terms of alliance-making throughout the discussion. They managed disagreement in multiple ways using indirect speech acts and linguistic discourse strategies which are evident in the alliance-making process. This study sheds light on how upper-intermediate ESL users interact in group interaction, especially on how they disagree and manage their way through it. The findings provide implications for future studies researching disagreement discourse in the future in terms of research methodology and focus. Apart from that, the implications are also highlighted in terms of pedagogical approaches, and practices, especially in ESL settings. This encompasses the teaching content (e.g.: the importance of pragmatic competence), methodology (e.g.: useful expressions and strategies), and possible activities (e.g.: group discussion) that are effective in assisting teachers to get students to communicate in ESL classrooms. This can be done in order to further develop the pragmatic competence of ESL learners, especially in terms of managing disagreements during face-to-face interaction.